Digital SMEs’ Borrowing Decisions: The Role of Literacy, Capabilities, and Fintech Lending - Gilang Kharisma Putra; Fitria Yuni Astuti; Jati Handarukmi (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Digital transformation has driven changes in financing behavior among Micro, Small, and Medium Enterprises (MSMEs), particularly in the use of technology-based financing sources. This study aims to analyze the influence of digital financial literacy, digital business capabilities, and access to fintech lending on the borrowing decisions of digital MSMEs in Central Java. The study employs a quantitative approach using a survey method targeting 180 digital MSME operators selected via purposive sampling. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that digital financial literacy, digital business capabilities, and access to fintech lending have a positive and significant influence on the borrowing decisions of digital MSMEs. Digital financial literacy has the greatest influence, followed by digital business capabilities and access to fintech lending. Additionally, these three variables account for 50.6% of the variation in SME borrowing decisions. These findings indicate that SME borrowing decisions in the digital era are influenced not only by capital needs but also by the level of digital readiness of business owners. This study contributes to the literature on SME financial behavior by emphasizing the importance of strengthening digital financial literacy, digital business capabilities, and access to digital financing in supporting more productive and sustainable financing decisions.